Desalination anion exchange membrane and method for manufacturing desalination anion exchange membrane

By forming a specific aluminosilicate film on the surface of the cation exchange membrane, the problems of insufficient durability and high cost of cation exchange membranes in the prior art are solved, and efficient and economical membrane performance improvements in seawater desalination process are achieved, supporting the realization of SDGs and carbon neutrality goals.

JP2025068456AActive Publication Date: 2025-04-28TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023178394
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-28
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

In the prior art, cation exchange membranes for seawater desalination have insufficient durability and are costly, making it difficult to meet the needs of seawater desalination in SDGs and carbon neutrality.

Method used

A cation exchange film with a specific aluminosilicate film is used to improve the durability and performance of the film by repeatedly adsorbing aluminum and silicon-containing gases on the surface of the cation exchange film, and forming an aluminosilicate film by oxidation.

Benefits of technology

The durability improvement and cost control of the cation exchange membrane are achieved, and the efficient performance can be maintained during seawater desalination, supporting the realization of SDGs and carbon neutrality goals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068456000001_ABST
    Figure 2025068456000001_ABST
Patent Text Reader

Abstract

To provide a desalination anion exchange membrane excellent in durability: and to provide a method for manufacturing a desalination anion exchange membrane.SOLUTION: A desalination anion exchange membrane is such as to have an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane. An Si / Al molar ratio of the aluminum silicate membrane is 0.1-0.9. A method for manufacturing a desalination anion exchange membrane comprises: a step 1 for making the surface of the anion exchange membrane adsorb aluminum-containing gas; a step 2 for making the surface of the anion exchange membrane adsorb silicon-containing gas; and a step 3 for generating an aluminum silicate by oxidizing the aluminum-containing gas and the silicon-containing gas adsorbed on the anion exchange membrane, and repeats the step 1, the step 2 and the step 3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to desalination anion exchange membranes and methods for making desalination anion exchange membranes. [Background technology]

[0002] Conventionally, research has been actively conducted on producing fresh water by treating seawater, and this has been put to practical use. For example, Patent Document 1 discloses a method for producing deionized water and solid salt or high-concentration salt water that can be used for salt electrolysis, which is characterized by treating low-concentration salt water with a salt water treatment device including an electrodialysis device using a cation exchange membrane selectively permeable to monovalent ions and an anion exchange membrane selectively permeable to monovalent ions, an evaporation concentration device, and a reverse osmosis membrane device. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-95821 A Summary of the Invention [Problem to be solved by the invention]

[0004] If seawater desalinization can be performed at low cost, it is expected to become widespread as drinking water, which is also useful from the perspective of the SDGs. In addition, if raw water for producing hydrogen for use in hydrogen batteries and the like can be obtained by desalinating seawater, it is expected to contribute to carbon neutrality. However, according to the studies of the present inventors, the anion exchange membranes used in conventionally known desalinization have problems with their durability, and improvements are desired from the perspective of cost as well.

[0005] An object of the present disclosure is to provide a desalination anion exchange membrane having excellent durability and a method for producing a desalination anion exchange membrane. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have found that a desalination anion exchange membrane having a specific aluminum silicate membrane thereon has excellent durability, which has led to the present disclosure.

[0007] An example aspect of this embodiment is described as follows.

[0008] (1) A desalination anion exchange membrane having an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, A desalination anion exchange membrane, the aluminum silicate membrane having a Si / Al molar ratio of 0.1 to 0.9. (2) A method for producing a desalination anion exchange membrane comprising an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, The aluminum silicate film has a Si / Al molar ratio of 0.1 to 0.9; A step 1 of adsorbing an aluminum-containing gas onto the surface of an anion exchange membrane; A step 2 of adsorbing a silicon-containing gas onto the surface of the anion exchange membrane; The method includes a step 3 of oxidizing the aluminum-containing gas and the silicon-containing gas adsorbed on the anion exchange membrane to produce aluminum silicate, A method for producing a desalination anion exchange membrane, comprising repeating steps 1, 2, and 3. (3) The method for producing a desalination anion exchange membrane according to (2), wherein the number of repetitions of steps 1, 2 and 3 is 20 to 500. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a desalination anion exchange membrane having excellent durability and a method for producing a desalination anion exchange membrane. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows a cross-sectional schematic of a desalination anion exchange membrane of the present disclosure. [Diagram 2]FIG. 1 shows a flow diagram of a method for producing a desalination anion exchange membrane of the present disclosure. [Diagram 3] A schematic diagram of an ALD apparatus is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The desalination anion exchange membrane and the manufacturing method of the desalination anion exchange membrane of the present embodiment will be described in detail below. One aspect of the present embodiment is a desalination anion exchange membrane having an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, the aluminum silicate membrane having a Si / Al molar ratio of 0.1 to 0.9. Another aspect of the present embodiment is a desalination anion exchange membrane having an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, the aluminum silicate membrane having a Si / Al molar ratio of 0.1 to 0.9, the manufacturing method of the desalination anion exchange membrane includes step 1 of adsorbing an aluminum-containing gas on the surface of the anion exchange membrane, step 2 of adsorbing a silicon-containing gas on the surface of the anion exchange membrane, and step 3 of generating aluminum silicate by oxidizing the aluminum-containing gas and silicon-containing gas adsorbed on the anion exchange membrane, and the manufacturing method of the desalination anion exchange membrane repeats steps 1, 2, and 3.

[0012] (Desalination anion exchange membrane) The desalination anion exchange membrane of this embodiment is a desalination anion exchange membrane having an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, and the Si / Al molar ratio of the aluminum silicate membrane is 0.1 to 0.9. A cross-sectional schematic diagram of the desalination anion exchange membrane is shown in FIG. 1. The desalination anion exchange membrane has an aluminum silicate membrane laminated on an anion exchange membrane. In the present disclosure, the desalination anion exchange membrane means an anion exchange membrane that can be used to desalinize non-freshwater such as seawater.

[0013] The anion exchange membrane constituting the desalination anion exchange membrane is not particularly limited, and for example, a conventionally known anion exchange membrane can be used. For example, anion exchange membranes such as Neocepta (registered trademark), Selemion (registered trademark), and Sustenion can be used. For the anion exchange membrane, a commercially available product or one produced separately can be used.

[0014] The Si / Al molar ratio of the aluminum silicate membrane laminated on the anion exchange membrane is 0.1 to 0.9, in one embodiment 0.13 to 0.8, in one embodiment 0.15 to 0.7, and in one embodiment 0.17 to 0.6. The above ranges are preferable because they provide extremely excellent anion exchange properties.

[0015] The thickness of the anion exchange membrane constituting the desalination anion exchange membrane is not particularly limited, but may be within a range conventionally known as the thickness of anion exchange membranes used in desalination of seawater, for example. In one embodiment, the thickness of the anion exchange membrane is 0.05 to 0.3 mm, in one embodiment, 0.07 to 0.2 mm, and in one embodiment, 0.09 to 0.11 mm.

[0016] The thickness of the aluminum silicate membrane is not particularly limited, but in one embodiment, it is 5 to 100 nm, in one embodiment, it is 10 to 50 nm, and in one embodiment, it is 20 to 30 nm. Within the above range, it is preferable because it is well balanced between the improvement of durability of the desalination anion exchange membrane and the increase in cost due to the provision of the aluminum silicate membrane. The thickness of the aluminum silicate membrane can be measured, for example, by cross-sectional TEM observation.

[0017] Aluminum silicate membranes are generally stronger than resins, and have excellent durability against bactericides (e.g., hypochlorous acid) added to seawater during seawater desalination. For this reason, the desalination anion exchange membrane of this embodiment, in which an aluminum silicate membrane is laminated on an anion exchange membrane, has excellent durability. It is considered that the aluminum silicate membrane itself constituting the desalination anion exchange membrane of this embodiment also has anion adsorption properties. This is because, when the Si / Al molar ratio of the aluminum silicate membrane is within the above-mentioned range, the aluminum silicate membrane has an Al-O tetrahedral basic structure. 3+ ToSi 4+ It has a structure in which Cl is substituted, and has a large positive charge. - This is believed to be because of its excellent anion adsorption properties.

[0018] (Method of manufacturing desalination anion exchange membrane) The method for producing a desalination anion exchange membrane of the present embodiment is a method for producing a desalination anion exchange membrane having an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, the aluminum silicate membrane having a Si / Al molar ratio of 0.1 to 0.9, and includes step 1 of adsorbing an aluminum-containing gas onto the surface of the anion exchange membrane, step 2 of adsorbing a silicon-containing gas onto the surface of the anion exchange membrane, and step 3 of generating aluminum silicate by oxidizing the aluminum-containing gas and silicon-containing gas adsorbed on the anion exchange membrane, and steps 1, 2, and 3 are repeated. The method for performing steps 1, 2, and 3 can be obtained. Although there is no particular limitation on the method for performing steps 1, 2, and 3, in one embodiment, they can be performed using an atomic layer deposition method (ALD method). In the present disclosure, a film formation apparatus for performing the ALD method is also referred to as an ALD apparatus. A flow diagram of the method for producing a desalination anion exchange membrane of the present embodiment is shown in FIG. 2, and a schematic diagram of the ALD apparatus is shown in FIG. 3. When carrying out the ALD method, you may refer to Y. Mori et al., “Room-Temperature Atomic Layer Deposition of Aluminum Silicate and its Application to Na- and K-Ion Sorption”, Journal of The Electrochemical Society, 167, 137502 (2020).

[0019] (Process 1) Step 1 is a step of adsorbing an aluminum-containing gas on the surface of an anion exchange membrane. The aluminum-containing gas is not particularly limited, but is preferably a molecule with a larger steric hindrance than the silicon-containing gas used in step 2. The aluminum-containing gas may be an aluminum alkoxide. An alkoxide group is preferred because it is a group with a relatively large molecular weight. As the aluminum alkoxide, aluminum butoxide is preferred because it has a large steric hindrance, is easily available, and is easily vaporized.

[0020] There are no particular limitations on the method for adsorbing an aluminum-containing gas into an anion exchange membrane, and it is preferable to use an ALD apparatus, place the anion exchange membrane in a film formation chamber, and introduce an aluminum-containing gas into the film formation chamber to adsorb the gas.

[0021] (Process 2) Step 2 is a step of adsorbing a silicon-containing gas onto the surface of the anion exchange membrane. The silicon-containing gas is not particularly limited, but a preferred embodiment is a molecule with smaller steric hindrance than the aluminum-containing gas used in step 1. If the molecule has smaller steric hindrance than the aluminum-containing gas, the silicon-containing gas is adsorbed into the gaps of the aluminum-containing gas adsorbed onto the anion exchange membrane, and it is easy to adjust the Si / Al molar ratio of the aluminum silicate membrane to the above range, which is preferable. Examples of the silicon-containing gas include alkylsilanes. An alkyl group is preferable because it is a group with a relatively small molecular weight. As an alkylsilane, tetramethylsilane, which has a methyl group with the smallest molecular weight, is one of the preferred embodiments because it has small steric hindrance, is easily available, and is easily adsorbed into the gaps of the aluminum-containing gas adsorbed onto the anion exchange membrane.

[0022] There are no particular limitations on the method for adsorbing the silicon-containing gas into the anion exchange membrane, and it is preferable to use an ALD apparatus and introduce the silicon-containing gas into the film formation chamber in which step 1 is carried out to adsorb the gas.

[0023] (Step 3) Step 3 is a step of generating aluminum silicate by oxidizing the aluminum-containing gas and silicon-containing gas adsorbed on the anion exchange membrane. The oxidation method is not particularly limited, but may be a method using an oxidizing agent. The oxidizing agent may be, for example, OH radical. The OH radical may be generated, for example, by making humidified Ar gas into plasma.

[0024] There is no particular limitation on the method for producing aluminum silicate by oxidizing the aluminum-containing gas and silicon-containing gas adsorbed on the anion exchange membrane, and the method can be carried out by using an ALD apparatus and introducing an oxidizing agent into the film formation chamber in which steps 1 and 2 have been performed.

[0025] In the method for producing a desalination anion exchange membrane of the present embodiment, steps 1, 2, and 3 are performed in this order, and then steps 1, 2, and 3 are usually performed again, that is, steps 1, 2, and 3 are repeated. In one embodiment, the number of repetitions of steps 1, 2, and 3 is 20 to 500, in one embodiment, 100 to 400, and in one embodiment, 150 to 250. By repeating steps 1, 2, and 3 within the above ranges, an aluminum silicate membrane having the above-mentioned thickness can be obtained, which is preferable.

[0026] As an optional step, after performing step 1 and before step 2, there may be a step of evacuating unadsorbed aluminum-containing gas, and after performing step 2 and before step 3, there may be a step of evacuating unadsorbed silicon-containing gas. EXAMPLES

[0027] The present embodiment will be described below with reference to examples, but the present disclosure is not limited to these examples.

[0028] (anion exchange membrane) As the anion exchange membrane, Neocepta AXP-D manufactured by Astom Corporation was used.

[0029] [Example 1] (Manufacture of desalination anion exchange membranes) An aluminum silicate film was laminated on the Neocepta AXP-D using atomic layer deposition (ALD) as described below. An ALD device was used to form the aluminum silicate film using the ALD method. A schematic diagram of the ALD device is shown in Figure 3. The OH radicals, an oxidizing agent, were generated by turning humidified Ar gas into plasma.

[0030] A NeoSepta AXP-D (anion exchange membrane) was installed in the deposition chamber of the ALD equipment. Al butoxide (aluminum butoxide) gas was introduced into the deposition chamber, and the Al butoxide was adsorbed onto the Neocepta AXP-D. Next, the Al butoxide was evacuated from the deposition chamber. Next, tetramethylsilane (TMS) gas was introduced into the deposition chamber, and the TMS was adsorbed onto the Neocepta AXP-D. Next, the TMS gas was evacuated from the deposition chamber. Finally, OH radicals were introduced into the deposition chamber, and the Al butoxide and TMS adsorbed onto the Neocepta AXP-D were oxidized.

[0031] The process from the adsorption of Al butoxide to the oxidation using OH radicals was counted as one cycle, and 200 cycles in total were performed to form an aluminum silicate membrane on the anion exchange membrane, thereby obtaining a desalination anion exchange membrane. As a result of cross-sectional TEM observation, the thickness of the aluminum silicate membrane was 26 nm.

[0032] (Si / Al molar ratio analysis) The concentrations of Si and Al in the aluminum silicate membrane constituting the desalination anion exchange membrane were measured by Auger spectroscopy, and the Si / Al molar ratio of the aluminum silicate membrane was calculated to be 0.2.

[0033] (Measurement of Cl ion adsorption amount) The desalination anion exchange membrane was immersed in a 12% aqueous solution of sodium hypochlorite (40°C, 24 hours).

[0034] The desalination anion exchange membrane after immersion was immersed in an aqueous NaCl solution (Nacalai Tesque, 5 mol / L) (40°C, 24 hours) and dried, and then the Cl concentration on the surface of the desalination anion exchange membrane was measured by X-ray photoelectron spectroscopy. The Cl concentration on the surface of the desalination anion exchange membrane was 2.1 at%.

[0035] [Comparative Example 1] (Measurement of Cl ion adsorption amount) Neosepta AXP-D was immersed in a 12% aqueous solution of sodium hypochlorite (40°C, 24 hours).

[0036] After the immersion, the Neosepta AXP-D was immersed in an aqueous NaCl solution (Nacalai Tesque, 5 mol / L) (40°C, 24 hours) and dried, after which the Cl concentration on the surface of the Neosepta AXP-D was measured by X-ray photoelectron spectroscopy. The Cl concentration on the surface of the Neosepta AXP-D was 0.2 at%.

[0037] The desalination anion exchange membrane of the embodiment showed approximately 10 times the Cl adsorption amount compared to the comparative example, even after treatment with hypochlorous acid, which is often used as a disinfectant in pretreatment when desalinating seawater, etc.

[0038] The upper limit and / or lower limit of the numerical ranges described in this specification can be arbitrarily combined to define a preferred range. For example, the upper limit and lower limit of the numerical range can be arbitrarily combined to define a preferred range, the upper limit of the numerical range can be arbitrarily combined to define a preferred range, and the lower limit of the numerical range can be arbitrarily combined to define a preferred range.

[0039] Although the present embodiment has been described in detail above, the specific configuration is not limited to this embodiment, and even if there are design changes within the scope that does not deviate from the gist of this disclosure, they are included in this disclosure.

Claims

1. The desalination anion exchange membrane has an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, A desalination anion exchange membrane, wherein the aluminum silicate membrane has a Si / Al molar ratio of 0.1 to 0.

9.

2. A method for producing a desalination anion exchange membrane comprising an anion exchange membrane and an aluminum silicate membrane laminated on the anion exchange membrane, The aluminum silicate film has a Si / Al molar ratio of 0.1 to 0.9; Step 1: adsorbing an aluminum-containing gas onto the surface of an anion exchange membrane; A step 2 of adsorbing a silicon-containing gas onto the surface of the anion exchange membrane; The method includes a step 3 of oxidizing the aluminum-containing gas and the silicon-containing gas adsorbed on the anion exchange membrane to produce aluminum silicate, A method for producing a desalination anion exchange membrane, comprising repeating steps 1, 2, and 3.

3. The method for producing a desalination anion exchange membrane according to claim 2, wherein the number of repetitions of steps 1, 2 and 3 is 20 to 500.

Citation Information

Patent Citations

  • Method of treating salt water

    JP2009095821A

  • Electric type deionized water production apparatus and deionized water production method

    JP2017018847A

  • ION ADSORBENT, Cs RECOVERY METHOD AND DEVICE USING THE SAME, AND ELECTRONIC APPARATUS

    JP2023116407A